PENGARUH FORMULA OBAT HERBAL UNTUK PENYEMBUHAN LUKA BAKAR - Kastika, Suci Mayastik; Rahayu, Resti (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
This research was to determine the effect of herbal medicine’s formulation (Night Blooming Jasmine, Tumeric and Patchouli) with variation of night blooming jasmine’s concentration and oil for treating burnt injury. It had been carried out from October to November 2016. This research observed wound radius using Morton’s method to measure wound radius as well as the counting of leucocytes. The research showed that 4.00% concentration of night blooming jasmine enhanced the healing process as much as 82.89±5.49%. This concentration was proved in reducing leucocyte rate from 14,050/mm3 to 7,560/mm3 and fully regrew mice hairs well.